Phylogenetic analysis of the New Guinean forest wallabies, Dorcopsis and Dorcopsulus reveals cryptic divergent lineages impacted by highland and lowland barriers - Mark D.B. Eldridge; Matthew J. Phillips; Renae C. Pratt; Linda E. Neaves; Kristofer M. Helgen; Sally Potter (Molecular Phylogenetics and Evolution, 2026)

Environmentally conscious hydrophobic spray coatings on bacterial cellulose for sustainable and reusable textiles - Katie A. Gilmour; Bruna Martins Dell’Agnese; George Bonney; Matthew Unthank; Neave White; Jane Scott; Angela Sherry; Paul James; Yunhong Jiang; Martyn Dade-Robertson; Meng Zhang (Journal of Cleaner Production, 2025)

Characterisation of a Mesophilic Aeromonas salmonicida and the Development of a PCR to Differentiate Atypical and Typical Strains - Teresa Wilson; Mark Green; Vivianne Dunn; David Cummins; Matthew Neave (Journal of Fish Diseases, 2025)
This study describes the identification and characterisation of a new mesophilic Aeromonas salmonicida strain, named HMes1 isolated from Atlantic salmon ( Salmo salar L.) in Tasmania. Isolates were identified as Aeromonas salmonicida through phenotypic, phylogenetic and genetic characterisation. After characterisation, the diagnostic phenotypic identification system MicroSys A24 was updated and a new multiplex conventional PCR was developed to enable rapid and inexpensive identification of atypical A . salmonicida , and exclusion of the exotic strain, A . salmonicida ssp. salmonicida .

Future‐proofing the koala: Synergising genomic and environmental data for effective species management - Matthew J. Lott; Belinda R. Wright; Linda E. Neaves; Greta J. Frankham; Siobhan Dennison; Mark D. B. Eldridge; Sally Potter; David E. Alquezar‐Planas; Carolyn J. Hogg; Katherine Belov; Rebecca N. Johnson (Molecular Ecology, 2022)
Climatic and evolutionary processes are inextricably linked to conservation. Avoiding extinction in rapidly changing environments often depends upon a species’ capacity to adapt in the face of extreme selective pressures. Here, we employed exon capture and high‐throughput next‐generation sequencing to investigate the mechanisms underlying population structure and adaptive genetic variation in the koala ( Phascolarctos cinereus ), an iconic Australian marsupial that represents a unique conservation challenge because it is not uniformly threatened across its range. An examination of 250 specimens representing 91 wild source locations revealed that five major genetic clusters currently exist on a continental scale. The initial divergence of these clusters appears to have been concordant with the Mid‐Brunhes Transition (~430 to 300 kya), a major climatic reorganisation that increased the amplitude of Pleistocene glacial‐interglacial cycles. While signatures of polygenic selection and environmental adaptation were detected, strong evidence for repeated, climate‐associated range contractions and demographic bottleneck events suggests that geographically isolated refugia may have played a more significant role in the survival of the koala through the Pleistocene glaciation than in situ adaptation. Consequently, the conservation of genome‐wide genetic variation must be aligned with the protection of core koala habitat to increase the resilience of vulnerable populations to accelerating anthropogenic threats. Finally, we propose that the five major genetic clusters identified in this study should be accounted for in future koala conservation efforts (e.g., guiding translocations), as existing management divisions in the states of Queensland and New South Wales do not reflect historic or contemporary population structure.

Prevalent and persistent viral infection in cultures of the coral algal endosymbiont Symbiodinium - Karen D. Weynberg; Matthew Neave; Peta L. Clode; Christian R. Voolstra; Christopher Brownlee; Patrick Laffy; Nicole S. Webster; Rachel A. Levin; Elisha M. Wood-Charlson; Madeleine J. H. van Oppen (Coral Reefs, 2017)

New species of Ophelina (Annelida: Opheliidae: Ophelininae) from northern Australia - Matthew J. Neave; Christopher J. Glasby (Organisms Diversity & Evolution, 2013)